The pseudo-Gondwanan genus Atlatlia (Diptera: Dolichopodidae) from Australia, New Caledonia, and Baltic amber, with the description of two new genera - Dan Bickel; John Martin (Records of the Australian Museum)
The fly genus Atlatlia Bickel, 1986 (Diptera: Dolichopodidae: Medeterinae) is revised with additional new recent and fossil species, and now comprises two major species groups. The Atlatlia grisea group includes three recent species from Australia, A. grisea Bickel, 1986; A. flaviseta Bickel, 1986; and A. isolata sp. nov., three recent species from New Caledonia, A. acra sp. nov., A. argenticoxa sp. nov., and A. cowanae sp. nov., and three species from Baltic amber, A. corynoura, sp. nov., A. electrica sp. nov., and A. licina, sp. nov. The Atlatlia ulrichi group includes six species from Baltic amber, A. angulicauda sp. nov., A. cryptica sp. nov., A. penicillata sp. nov., A. ramosa sp. nov., A. tonsa, sp. nov., and A. ulrichi sp. nov. The genus Kashubia gen. nov., is described from Baltic amber with three species: K. falcata, sp. nov., K. ornatipes sp. nov., and K. starki sp. nov. The genus Eridanomyia gen. nov. is described from Baltic amber with two species, E. amica sp. nov. and E. conjugalis sp. nov. Four of the newly described Baltic amber species also occur in Bitterfeld amber, suggesting their overall faunal similarity. The striking disjunction of the genus Atlatlia in both time and space, recent Australia and New Caledonia and Paleogene Baltic amber, suggests a once much wider distribution, possibly during Eocene “greenhouse earth” climatic conditions, with subsequent extinction leaving only a relict fauna in Australasia. With geological evidence suggesting New Caledonia was largely submerged in the early Paleogene and only emergent in the late Eocene, the New Caledonian Atlatlia fauna possibly originated by dispersal from Australia in the early to mid-Cenozoic.